Human Rights and Police Supervision Model: Indonesias Case - Muradi (International Journal of Asian Social Science, 2016)
This paper will discuss two issues related to poor implementation of human rights by Police, based on four measuring analyzes of human rights implementation based on role and function as follow: the use of violence, human rights violations, act of disparage and militaristic culture in Police tasks. This paper also argues that human rights implementation in the Police are still not fully guaranteed and improved. This is due to four reasons: prolonging police culture, inappropriate police discretion, the role of Precinct as key implementer of police policies, as well as the improper role of Police as state-agency of violence in term of implementation. The second issue of this paper is a model of police supervision in order to be effectively implements Human Rights for Police in performing tasks, roles and functions to serve the public.